Characteristics of siblings with celiac disease diagnosed by family screening - ERTEM ŞAHİNOĞLU, DENİZ (My University, 2022)
Objective:The aim of this study was to evaluate the features of asymptomatic siblings of index celiac patients who were diagnosed with celiac disease (CD) at the initial screening.Methods:We reviewed hospital records of 210 children with CD. The characteristics of sibling celiacs (n=24) were compared with index celiacs (n=186).Results:At diagnosis, sibling celiacs were older than index celiacs (mean (SD) 10.4 (2.7) vs 8.2 (4.3) years;P=0.02). There were no significant differences between sibling and index celiacs in terms of serum anti-tTG IgA titer (≥10xULN, 83.3% vs 85%), and most of the patients had moderate/severe villous atrophy in both groups. The rates of iron deficiency anemia, folic acid deficiency, wasting and stunting were comparable between sibling and index celiac patients.Conclusions:Siblings with CD were older than index children with CD at diagnosis, and their characteristics were similar to symptomatic index children with CD, despite not having any complaints.Keywords:Asymptomatic, Serology, Silent disease
Keywords: Tıp; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Pediatrik Gastroenteroloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Child Health and Diseases; Pediatric Gastroenterology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; PEDİATRİ; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; PEDIATRICS; MEDICINE, GENERAL & INTERNAL; Genel Sağlık Meslekleri; Pediatri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Pediatri, Perinatoloji ve Çocuk Sağlığı; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pediatrics; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Pediatrics, Perinatology and Child Health; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine